A177: Program Evaluation of the ACR/CARRA Inter‐Institutional Mentoring Program (AMIGO) in Pediatric Rheumatology. Issue 11 (March 2014) - Muscal, Eyal; Moorthy, Lakshmi N.; Riebschleger, Meredith P.; Eberhard, Anne; Huttenlocher, Anna; Klein‐Gitelman, Marisa S.; Prahalad, Sampath; Stevens, Kelly Rouster; Schneider, Rayfel; Nigrovic, Peter A.
Abstract : Background/Purpose: In pediatric rheumatology, the small size of many academic programs translates into limited mentoring options for early career physicians. To address this "mentorship gap, " in 2011 the American College of Rheumatology (ACR) and the Childhood Arthritis and Rheumatology Research Alliance (CARRA) joined together to develop AMIGO, the ACR/CARRA Mentoring Interest Group, that now includes greater than half of pediatric rheumatology fellows and junior faculty in the US and Canada. We report ongoing program evaluation encompassing pilot (2011) and full roll‐out (2012, 2013) phases of the AMIGO project. Methods: Mentees and mentors participating in the AMIGO project were surveyed via online questionnaire to determine dynamics of contact and perceived benefit. The entire pediatric rheumatology community was surveyed in 2011 to determine the state of mentoring and career development, with a repeat survey planned for early 2014. We tabulated the active dyads as of January 2014. Results: As recently reported, detailed evaluation of the pilot phase 17 months after initial roll‐out found that 19 of 20 pilot AMIGO dyads were still functioning, with substantial benefit noted by mentees in career guidance, scholarship, and job satisfaction. Benefits reported by mentors included improvement of their mentoring skills and development of their academic portfolios. Both mentees and mentors reported improved connectedness to the wider pediatric rheumatology community. 83 additional dyads were matched prior to 2012 and 2013 ACR meetings. Comparison of these 17‐month pilot results to a December 2013/January 2014 survey of all active AMIGO participants is ongoing. A questionnaire administered to the whole pediatric rheumatology community in 2011 (n = 135 respondents, including an estimated 64–70% response rate among fellows and junior faculty) found that approximately 60% of fellows and junior faculty had a career development mentor. We will assess whether the AMIGO program has had a global impact upon the mentoring culture in pediatric rheumatology by collecting community‐wide survey data in 2014 and then comparing to 2011 data. Conclusion: The 2011 AMIGO pilot program has confirmed the feasibility of a North American inter‐institutional mentoring program in pediatric rheumatology. Participants identified benefits to both mentees and mentors in multiple domains, most prominently in career guidance, a core goal of the program. Ongoing program evaluation will determine how much of this benefit has been sustained after participation was opened to the whole community, and whether the program has had a measureable impact on the overall state of mentoring in pediatric rheumatology.